Investigating The Types of Food Additives Used in Some Children’s ‎Favorite Food Products - Aborous, Naji; Emhem, Ibrahim; Al Makrof, Asma (Journal of Pure & Applied Sciences, 2024)
Children's food quality control is the process of tracking and inspecting children's food ‎to ensure their safety and quality. This process aims to protect children's health and ‎ensure that products comply with the nutritional standards and requirements specified ‎according to the standard specifications for each food product. Quality control of ‎children's food includes many steps and procedures, which include checking ingredients, ‎production, laboratory testing, data label, packaging material, transportation, handling, ‎and storage, until it reaches consumption. This study aimed to investigate the types of ‎food additives in some food products that children prefer and which may harm their ‎health. The food additives recorded in the labeling card of (76) food products were ‎examined in some stores and markets selling food products in the city of Nalut, some of ‎which were produced in Libya and some of which were imported from (15) countries. ‎The descriptive analytical approach was followed in analyzing the data, and the ‎percentages of product non-compliance with what was stated in the standard ‎specifications were calculated. The results of the study showed that most of the food ‎products consumed by children's from stores and markets in the city of Nalut had a ‎percentage of non-compliance with national and international standard specifications as ‎follows: flavorings 43%, food colorings 30%, acidity-regulating additives 63%, ‎emulsifying agents 42%, food additives Thickener 13% and antioxidant additives 5%, ‎with some imported products containing banned colorant’s, and some national products ‎containing unclear labeling data, and most national and imported products in general ‎containing artificial dyes. Excessive consumption of them causes many health problems, ‎and most of them contain It contains many additives in one product, which may lead to ‎harm to children’s health, which requires the relevant authorities to intensify their efforts ‎to protect children’s health